(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Tissue doppler derived systolic strain detects the subtle changes in left ventricular (LV) function. This new modality can detect LV dysfunction in severe rheumatic mitral regurgitation (MR) at earlier stages. The present study was conducted to compare tissue doppler derived peak systolic strain between patients with different severities of LV dysfunction in rheumatic severe MR and to look for the negative correlation between LV dysfunction and peak systolic strain. Subjects and methods: A descriptive correlational study was conducted from January 2017 to March 2018 at Punjab Institute of Cardiology, Lahore. Fifty healthy controls taken as group-I and 150 asymptomatic patients of rheumatic severe MR were divided into Group-II (with ejection fraction (EF) ≥60% and left ventricular end systolic dimension (LVESD) ≤40mm), Group-III (with EF≥ 60% and LVESD 41-50mm) and Group-IV (with EF <60%).Longitudinal peak systolic strain (PSS) of the groups were measured by tissue doppler imaging and compared. The correlation between systolic dysfunction and PSS was further studied. Results: Out of 200 subjects, 91(45.5%) were male and 109 (54.5%) female. Mean age of study subjects was 31± 9.5 years. Moving from group-I to group-IV, mean LVESD increased from 23.3±2.4 to 49.3±3.0, mean LVEDD (left ventricle end diastolic dimension) increased from 46.4±3.4to 64.0±3.6, ejection fraction decreased from 63.6±2.1to45.7±6.7 and average PSS decreased from 17.8±0.53 to 8.31±0.52.Significant difference was found in average PSS between these groups (p<0.001).There was a significant (p<0.001)negative correlation (correlation coefficient = -0.968) between average PSS and LV dysfunction (i.e. group number). Conclusion: Inrheumatic severe mitral regurgitation, tissue doppler derived peak systolic strain decreases with increase of LV dysfunction showing a significant negative correlation between the two.